THE QUALITY OF GROWTH: PERAN TEKNOLOGI DAN INVESTASI HUMAN CAPITAL SEBAGAI PEMACU PERTUMBUHAN EKONOMI BERKUALITAS - Prasetyo, P Eko (JEJAK, 2008)
In the process of developing economy in a whole and continuously, the macro economy stability of acountry is an essential prerequisite for producing a quality economic growth. For achieving the qualityeconomic growth, there should be a continuous capital human investment and the use of continuousscience and technology (IPTEK). The process of developing economy will be able to transform thesociety condition from vicious circle to virtuous circle condition if the growth of economy is qualified..Keywords: Quality of growth; human capital, technology and virtuous circle.